Audrey Truschke, Culture of Encounters. Sanskrit at the Mughal Court, Nueva Delhi-Londres, Allen Lane-Penguin-Columbia University Press, 2016, 362 pp. - Muñoz García, Adrián (Estudios de Asia y África, 2017)
Audrey Truschke, Culture of Encounters. Sanskrit at the Mughal Court, Nueva Delhi-Londres, Allen Lane-Penguin-Columbia University Press, 2016, 362 pp.